2013
DOI: 10.4319/lo.2013.58.4.1463
|View full text |Cite
|
Sign up to set email alerts
|

Microphytobenthic extracellular polymeric substances (EPS) in intertidal sediments fuel both generalist and specialist EPS‐degrading bacteria

Abstract: Microphytobenthic biofilms contain high concentrations of carbohydrate-rich extracellular polymeric substances (EPS) that are important in sediment carbon cycling. Field measurements at two locations in the Colne Estuary, U.K., showed that a significant curvilinear relationship explained 50% of the variability in chlorophyll a and EPS content. Estimates of EPS production, based on field data and published rates of production by diatoms, revealed that EPS turnover of 52% to 369% over the tidal cycle was require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
51
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 80 publications
3
51
1
Order By: Relevance
“…Common photosynthetic exudates include amino acids, organic acids, sugars and sugar‐alcohols (Watanabe et al ., ; Stengel et al ., ). Recently, Taylor and colleagues () demonstrated the utilization of algal produced extracellular polymeric substances by bacteria (especially Alphaproteobacteria and Gammaproteobacteria ) in marine microphytobenthic biofilms. Also, the significant increase in the leucine‐aminopeptidase in biofilms at L‐HT may indicate a greater decomposition of proteinaceous compounds excreted by primary producers (Ylla et al ., ; Díaz‐Villanueva et al ., ), as well as a decrease in the decomposition of polysaccharides.…”
Section: Discussionmentioning
confidence: 97%
“…Common photosynthetic exudates include amino acids, organic acids, sugars and sugar‐alcohols (Watanabe et al ., ; Stengel et al ., ). Recently, Taylor and colleagues () demonstrated the utilization of algal produced extracellular polymeric substances by bacteria (especially Alphaproteobacteria and Gammaproteobacteria ) in marine microphytobenthic biofilms. Also, the significant increase in the leucine‐aminopeptidase in biofilms at L‐HT may indicate a greater decomposition of proteinaceous compounds excreted by primary producers (Ylla et al ., ; Díaz‐Villanueva et al ., ), as well as a decrease in the decomposition of polysaccharides.…”
Section: Discussionmentioning
confidence: 97%
“…The even labeling between different bacterial groups may be explained by a combination of diatom primary production dominating heterotrophic carbon cycling in this sediment and a wide variety of exudates produced by diatoms (although our results indicate that glucose in water-extractable EPS was a major intermediate). Taylor et al (2013) reported high label incorporation by diatoms, Alpha, and Gammaproteobacteria from isolated water-extractable EPS with RNA-SIP, but also showed the even labeling of general bacterial PLFA with PLFA-SIP. Miyatake et al (2013) also reported the even utilization of glucose (and other organic substrates) by most major groups in the microbial community of the sediment surface layer (0-2 cm).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we also measured 13 C labeling in bulk, water-extractable, and EDTA-extractable carbohydrates as well as SCOA in pore water using recently developed LC-IRMS methods to determine which intermediates were important in the transfer of organic matter from diatoms to heterotrophic bacteria. Although the relationship between diatom carbohydrates exudates and the heterotrophic bacterial community have been studied in intertidal sediments (Hanlon et al 2006;Haynes et al 2007;Bellinger et al 2009;Oakes et al 2012;Taylor et al 2013), we included SCOA as important intermediates in the anaerobic degradation of diatom material . The results were used to construct a conceptual model of the transfer of carbon in the diatom mat (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…, Rivkin and Putt , Tuchman , Taylor et al. ) and may, in fact, be the norm rather than the exception (Mitra et al. , Selosse et al.…”
Section: Discussionmentioning
confidence: 99%